Correcting partial volume effects in biexponential T2 estimation of small lesions. Issue 4 (17th April 2014) - Huang, Chuan; Galons, Jean‐Philippe; Graff, Christian G.; Clarkson, Eric W.; Bilgin, Ali; Kalb, Bobby; Martin, Diego R.; Altbach, Maria I.
Abstract : Purpose: T 2 mapping provides a quantitative approach for focal liver lesion characterization. For small lesions, a biexponential model should be used to account for partial volume effects (PVE). However, conventional biexponential fitting suffers from large uncertainty of the fitted parameters when noise is present. The purpose of this work is to develop a more robust method to correct for PVE affecting small lesions. Methods: We developed a region of interest‐based joint biexponential fitting (JBF) algorithm to estimate the T 2 of lesions affected by PVE. JBF takes advantage of the lesion fraction variation among voxels within a region of interest. JBF is compared to conventional approaches using Cramér–Rao lower bound analysis, numerical simulations, phantom, and in vivo data. Results: JBF provides more accurate and precise T 2 estimates in the presence of PVE. Furthermore, JBF is less sensitive to region of interest drawing. Phantom and in vivo results show that JBF can be combined with a reconstruction method for highly undersampled data, enabling the characterization of small abdominal lesions from data acquired in a single breath hold. Conclusion: The JBF algorithm provides more accurate and stable T 2 estimates for small structures than conventional techniques when PVE is present. It should be particularly useful for the characterization of small abdominal lesions.Magn Reson Med 73:1632–1642, 2015. © 2014 Wiley Periodicals, Inc.